Penerapan kapasitas produk melalui perencanaan agregat: Studi kasus pada konveksi kaos polos Cijoged Subang - Puspasari, Dewi (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2023)
Businesses that want to compete globally and grow their operations must prioritize planning. This includes planning for production processes, sourcing materials, labor availability, and quality control. Planning product capacity is essential for small and medium-sized enterprises (MSMEs) because it impacts their costs and profits. However, limited capital can make this challenging. Businesses can use aggregate planning to optimize their operations to address this issue. In this study, we analyzed the application of product capacity through aggregate planning at the Cijoged Subang Plain T-shirt Convection. We used the Smooth Production method and POM QM for Windows software to collect and process data. Our findings suggest that implementing aggregate planning can help businesses map their costs and meet product demand capacity, including expenses related to regular and overtime working hours, subcontracting, and inventory.